Training of Adult Workers in Europe and Brazil. Between Emancipatory Education and Recycling for the Market - Hernández-Carrera, Rafael M.; Machado, Maria Margarida; González-Monteagudo, José (IJERI. International Journal of Educational Research and Innovation, 2018)
This article investigates conceptions about education and training of adult workers, forged in two very different educational contexts, such as Europe and Brazil. It has been possible to identify some relevant influences of the European conception of adult education on the historical evolution of Brazilian education, taking into account the differences among historical, economic, political and social factors that have influenced European countries and Brazil. There are peculiar features of the Brazilian reality, derived from the low rate of schooling, and the situation of educational exclusion experienced by the Brazilian workers up to the present. This implies a strong difference between the European and Brazilian reality mainly due to the development of vocational training in Europe as a strategy of permanent education. After the historical phase of permanent education, which developed in the mid-twentieth century, current approaches to lifelong learning need to be properly contextualized, to avoid the risk of conceptual generalizations, which historically tend to conceal and legitimize exclusionary educational policies. This paper also discusses tensions and conflicts between educational approaches conditioned by emancipation, and by instrumental adaptation to the labour market and society.
Keywords: adult education; training of workers; permanent education; lifelong learning; Emerging